Integration of local agroindustry in ethnoscience-based chemistry teaching: A strategy to strengthen ecological literacy and entrepreneurial student characters - Jumriani (Proceedings of International Conference on Research in Education, 2025)
This study aims to develop and evaluate an ethnoscience-based chemistry teaching module supported by local agroindustry resources in West Sulawesi as a strategy to strengthen students’ ecological literacy and entrepreneurial character. The research employed a research and development (R&D) approach using the 4D model. Data were collected from 36 science teachers through questionnaires assessing the feasibility, relevance, and applicability of the developed module. The results indicated that teachers’ responses were very positive, particularly in terms of contextual integration of agroindustry practices, promotion of ecological awareness, and potential to foster entrepreneurial attitudes among students. The findings suggest that integrating local agroindustry within ethnoscience-oriented chemistry learning provides meaningful contextualization, enhances students’ understanding of the relationship between science and local wisdom, and encourages sustainable entrepreneurial values. This innovation has the potential to contribute to both ecological preservation and the development of future-oriented competencies in education.